Correlation between sensory attributes and Metabolomic profiles of cocoa liquor from different cacao genotypes - Enik Nurlaili Afifah; Indah Anita Sari; Agung Wahyu Susilo; Hendy Firmanto; Abdul Malik; Eiichiro Fukusaki; Sastia Prama Putri (Food Chemistry: X)
Flavor is a critical quality of cacao beans and is significantly influenced by the genotype. Relying solely on sensory evaluation to describe the complex flavors of different cacao genotypes is insufficient because of the reliance on human expertise and the need for robust validation. This study aimed to enhance the understanding of flavor quality in different cacao genotypes by investigating the correlation between sensory attributes and metabolite profiles using metabolomics-based approach and sensory analysis. Cacao genotypes can be categorized based on their sensory attributes and metabolite profiles. The ICCRI09-genotype exhibited outstanding flavors, which were significantly associated with non-volatile and volatile compounds (e.g. Organic acids, some sugars, 3-methylbutanal, 2,3-butanediol, benzaldehyde, linalool, trans-linalool oxide, isobutyl acetate, etc.) (P < 0.05). In contrast, theobromine, epicatechin, and catechin, which are linked to bitterness and astringency, were abundant in KW516-Forastero. These findings have significant implications and provide a scientific basis for authenticating the high flavor quality of cacao.